A comparative study of the conformational stabilities of trypsin and α-chymotrypsin - Lehoczkiné Simon, Mária (Acta Biologica Szegediensis, 2001)
A comparative study was performed on the conformational stabilities of trypsin and a-chymotrypsin. At 45ºC, trypsin was most stable at pH 3, while the highest stability of a -chymotrypsin was observed at pH 5. With both ester and amide substrates, trypsin displayed activation at pH 3. In the case of a-chymotrypsin, activation was detected at pH 5 only with the amide substrate. The time curves of heat inactivation were complex. For both enzymes, autolysis proceeded with the highest velocity at pH 8. The results obtained on a-chymotrypsin suggested consecutive reactions: the first step, heat denaturation of the protein, is followed by digestion of the damaged molecules.